The Role of Capital on Islamic Bank Spin-Offs in Indonesia - Prasetyo, Muhammad Budi; Luxianto, Rizky; Baskoro, Rahmat Aryo; Adawiyah, Wardatul; Putri, Niken Iwani S. (UI Scholars Hub, 2019)
Research Aims: Some Islamic banks have experienced decreasing performance after spinning off from the parent company, and it is presumed that the amount of capital may have contributed to the decline. Hence, this paper aims to find a minimum amount of capital that Islamic banks must own after spin-offs in order to be able to compete in the market and to achieve excellent performance. Design/Methodology/Approach: We employ the OLS method for small banks (assets below Rp 5 trillion) with variable Capital as the dependent variable and Bank Performance (ROA, ROE, BOPO, and NPL) as the independent variable. We conduct several rounds of regression analysis by including different dummy variables to capture an increase in bank performance when certain capital limits are applied. Various results of the interaction between Capital and Bank Performance are mapped into the frontier line formed by the regression equation. We then compare the frontier results with the actual bank identifier to map the position of each bank relative to the frontier. We add cluster analysis to confirm the results further. Research Findings: Descriptive statistics of the small banks shows that conventional banks perform better in overall performance, efficiency and risk in comparison with the Islamic banks. Several dummy variables are set to represent the size of bank capital (Rp. 800 billion, Rp. 1 trillion, Rp. 1.2 trillion, and Rp. 1.5 trillion), and all dummy variables are significant; the corresponding coefficient reveals that the higher the capital, the better the average performance. Also, the relationship between performance and bank capital is a non-linear (quadratic) relationship that is convex, indicating that capital is not the only critical factor that contributes to the bank’s improvement. The cluster analysis partially confirms that there is a specific pattern of capital in each of the clusters. Theoretical Contribution/Originality: The result of this study is in line with some previous literature on the relationship between capital and bank performance. In banks with small capital, capital has a positive influence on bank performance but has the opposite effect after reaching a certain point. In the literature related to spin-offs in Islamic banking, there are only a few studies about the performance of small banks after the spin-off and even fewer (or none) that discuss the critical role of capital and its relationship with the bank’s performance after the spin-off. Our findings support previous studies conducted by Siswantoro (2014). Managerial Implications in the South East Asian Context: With the implementation of the dual banking system in several southeast Asian countries, many conventional banks have Islamic bank subsidiaries. Findings from this research could help banking regulators in the South East Asian countries to carefully re-evaluate their spin-off strategy for the unit bank, especially regarding the limit of capital requirement before the spin-off. The bigger the capital size, the better the performance of the business unit after the spin-off. Research Limitation & Implications: This research only uses variable capital as a determinant for the bank’s performance after spin-offs. However, as suggested by the resulting R-Squared from the regression formula (66%) and the convex trend line of the frontier analysis, other factors may contribute to the banking performance. Future research should include several other indicators for spin-off success, such as parent-subsidiary relationship (Tubke, 2004; Lindholm-Dahlstrand, 2000) and parent’s size (Cristo and Falk, 2006), credit and liquidity position before spin-offs.